Daytime behavior of Pteropus vampyrus in a natural habitat: the driver of viral transmission - HENGJAN, Yupadee; PRAMONO, Didik; TAKEMAE, Hitoshi; KOBAYASHI, Ryosuke; IIDA, Keisuke; ANDO, Takeshi; KASMONO, Supratikno; BASRI, Chaerul; FITRIANA, Yuli Sulistya; ARIFIN, Eko M. Z.; OHMORI, Yasushige; MAEDA, Ken; et al. (Journal of Veterinary Medical Science, 2017)
Flying foxes, the genus Pteropus, are considered viral reservoirs. Their colonial nature and long flight capability enhance their ability to spread viruses quickly. To understand how the viral transmission occurs between flying foxes and other animals, we investigated daytime behavior of the large flying fox (Pteropus vampyrus) in the Leuweung Sancang conservation area, Indonesia, by using instantaneous scan sampling and all-occurrence focal sampling. The data were obtained from 0700 to 1700 hr, during May 11–25, 2016. Almost half of the flying foxes (46.9 ± 10.6% of all recorded bats) were awake and showed various levels of activity during daytime. The potential behaviors driving disease transmission, such as self-grooming, mating/courtship and aggression, peaked in the early morning. Males were more active and spent more time on sexual activities than females. There was no significant difference in time spent for negative social behaviors between sexes. Positive social behaviors, especially maternal cares, were performed only by females. Sexual activities and negative/positive social behaviors enable fluid exchange between bats and thus facilitate intraspecies transmission. Conflicts for living space between the flying foxes and the ebony leaf monkey (Trachypithecus auratus) were observed, and this caused daily roosting shifts of flying foxes. The ecological interactions between bats and other wildlife increase the risk of interspecies infection. This study provides the details of the flying fox’s behavior and its interaction with other wildlife in South-East Asia that may help explain how pathogen spillover occurs in the wild.